The effects of acute hyperhomocysteinemia induced by DL-homocysteine or DL-homocysteine thiolactone on serum biochemical parameters, plasma antioxidant enzyme and cardiac acetylcholinesterase activities in the rat - Kornjača, Dusko; Živković, Vladimir; Krstić, Danijela; Čolović, Mirjana; Đurić, Marko; Stanković, Sanja; Mutavdžin, Slavica; Jakovljević, Vladimir; Đurić, Dragan (Archives of Biological Sciences, 2018)
The aim of this study was to assess the effects of DL-homocysteine (DL-Hcy) and DL-homocysteine thiolactone (DL-Hcy TLHC) on selected serum biochemical parameters, markers of oxidative stress and the activities of antioxidant enzymes (catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD)) in the plasma, as well as on acetylcholinesterase (AChE) activity in the cardiac tissue homogenate in the rat. Male Wistar rats were divided into three groups as follows: control group (1 mL 0.9% NaCl, intraperitoneal (i.p.) injection), DL-Hcy group (8 mmol/kg body mass (b.m.), i.p.) or DL-Hcy TLHC group (8 mmol/kg b.m., i.p.). One hour after administration, the rats were euthanized, whole blood was collected for biochemical analysis, and the heart was excised. Following the i.p. administration of DL-Hcy and DL-Hcy TLHC, the activities of antioxidant enzymes were mostly significantly increased, while plasma malondialdehyde (MDA) was decreased. Administration of DL-Hcy and DL-Hcy TLHC significantly inhibited AChE activity in rat cardiac tissue. Our findings suggest that DL-Hcy and DL-Hcy TLHC exerted prooxidant effects; however, the decrease in MDA points to an inverse response to the increase in antioxidant enzyme activities. While both substances inhibited AChE activity in rat cardiac tissue, DL-Hcy TLHC induced stronger effects than DL-Hcy. https://doi.org/10.2298/ABS170731041K Received: July 31; Revised: October 23, 2017; Accepted: October 23, 2017; Published online: October 30, 2017 How to cite this article: Kornjača D, Živković V, Krstić D, Čolović M, Đurić M, Stanković S, Mutavdžin S, Jakovljević V, Đurić D. The effects of acute hyperhomocysteinemia induced by DL-homocysteine or DL-homocysteine thiolactone on serum biochemical parameters, plasma antioxidant enzyme and cardiac acetylcholinesterase activities in the rat. Arch Biol Sci. 2018;70(2):241-8.